PENGARUH TRANSACTIONAL LEADERSHIP PADA COMPETITIVE ADVANTAGE MELALUI MANAGEMENT CONTROL SYSTEM PADA KANTOR AKUNTAN DI INDONESIA - Hendri Kwistianus; Devie Devie; Velisa Tanaya; Ariono Santosa (Business Accounting Review, 2021)
This study aims to observe the effect of Transactional leadership on competitive advantage mediated by the management control system with the object of research. In this study, research data was obtained by distributing questionnaires to research respondents, namely accounting office employees as many as 112 respondents. The data obtained were then processed using data analysis techniques with the PLS model. The results show that Transactional leadership has an effect on the management control system but has no effect on competitive advantage. In this study also found that the management control system has an effect on competitive advantage. In this study it was also found that there is a perfect mediating effect of the management control system on the effect of Transactional leadership on competitive advantage.